If anyone is in Christ – new creation! - Page, BT (Cambridge University Press, 2018)
This article investigates the metaphysical transformation that occurs when a believer becomes a new creation, something which hasn't yet been explored in the literature. I start by setting out what this ontological transformation involves, and then provide two models as to how it might go. The first is a type of substratism, based on a theory of mixing, while the second thinks about this transformation in terms of replacementism. Throughout the article I seek to resolve difficulties that both of these models bring, while also showing how other aspects of Christian thought can be explained by these models.